2008
DOI: 10.1038/nrc2391
|View full text |Cite
|
Sign up to set email alerts
|

Heavy ion carcinogenesis and human space exploration

Abstract: Prior to the human exploration of Mars or long duration stays on the Earth's moon, the risk of cancer and other diseases from space radiation must be accurately estimated and mitigated. Space radiation, comprised of energetic protons and heavy nuclei, has been show to produce distinct biological damage compared to radiation on Earth, leading to large uncertainties in the projection of cancer and other health risks, while obscuring evaluation of the effectiveness of possible countermeasures. Here, we describe h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
333
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 522 publications
(342 citation statements)
references
References 115 publications
1
333
0
8
Order By: Relevance
“…There is a slight dependence of the relative abundances on the solar cycle. Despite their comparably low intensity, heavy ions have a great impact on the radiation exposure in space due to their high biological relevance (Durante & Cucinotta 2008). In general, the contributions of primary nuclei up to atomic numbers of Z = 26 (Fe) are sufficient to estimate the radiation exposure to humans from GCR.…”
Section: Galactic Cosmic Ray Modelmentioning
confidence: 99%
“…There is a slight dependence of the relative abundances on the solar cycle. Despite their comparably low intensity, heavy ions have a great impact on the radiation exposure in space due to their high biological relevance (Durante & Cucinotta 2008). In general, the contributions of primary nuclei up to atomic numbers of Z = 26 (Fe) are sufficient to estimate the radiation exposure to humans from GCR.…”
Section: Galactic Cosmic Ray Modelmentioning
confidence: 99%
“…22 However, it is apparent in Figure 3(b) that the three exposure response curves are remarkably similar, indicating that the attenuation length in the present experiments is greater than the range of film thicknesses studied and confounds our previous approach. Fortunately (7), can be evaluated numerically and Levenberg-Marquardt optimization, 43 further permits the most probable values of P 0 , P min , σ, and λ to be determined at each film thickness. It was found that the optimal values depend slightly on the initial seed values.…”
Section: Determination Of Absolute Cross Section For Strand Break mentioning
confidence: 99%
“…The accuracy of simulations thus depends on data describing individual scattering events, e.g., those of SEs with condensed molecules. Electron-molecule cross sections are absolute quantities that describe these events and are thus essential for modelling radiation induced processes occurring in diverse fields including plasma processing, 4 water e-beam purification, 5 astro-chemistry, 6 human spaceflight, 7 and radiobiology. 8 In radiobiology, MC simulations can describe both the so-called direct effects of primary radiation and secondary species on DNA, as well as the indirect effects of OH • and other radicals produced in liquid water.…”
Section: Introductionmentioning
confidence: 99%
“…charged particles | radial dose distribution | biodosimetry | γH2AX foci | local effect model C harged particles, including protons, α-particles, and heavy ions, are increasingly used in cancer radiotherapy and represent a significant component of the natural background irradiation on earth and in space (1)(2)(3). Their biological effect is often very different from that of photons (X-or γ-rays), largely because charged particles deposit their energy along a track, whereas photons produce a fairly homogeneous dose distribution.…”
mentioning
confidence: 99%